PROPOSTA DE SISTEMÁTICA PARA PREVENÇÃO E CONTROLE DE ENDEMIAS EM TRABALHADORES NA CONSTRUÇÃO DE DUTOS: ESTUDO DE CASO NA REGIÃO AMAZÔNICA - Chimelli, Maurício Abi-ramia (2009)
The economic growth and industrialization had generated a demand for natural resources resulting in environmental impacts. The believe that the development is not a simple search for the economic growth, and that believe that started to take in consideration the necessary harmony with the environmental balance and the quality of life of the people, appeared together with the conferences proposals by the United Nations Organization. In such way, appeared the term sustainability and sustainable development, that ties the environment, economic and the social sector and includes the following ideas: concern with the future, protection and conservation of the environmental resources, balanced development, equal use of the resources in a responsible way, rights and chances for the society.